The Daily Consumption of Cola Can Determine Hypocalcemia: A Case Report of Postsurgical Hypoparathyroidism-Related Hypocalcemia Refractory to Supplemental Therapy with High Doses of Oral Calcium - Guarnotta, Valentina; Riela, Serena; Massaro, Marina; Bonventre, Sebastiano; Inviati, Angela; Ciresi, Alessandro; Pizzolanti, Giuseppe; Benvenga, Salvatore; Giordano, Carla (Frontiers in Endocrinology, 2017)
The consumption of soft drinks is a crucial factor in determining persistent hypocalcemia. The aim of the study was to evaluate the biochemical mechanisms inducing hypocalcemia in a female patient with usual high consumption of cola drink and persistent hypocalcemia, who failed to respond to high doses of calcium and calcitriol supplementation. At baseline and after pentagastrin injection, gastric and duodenal secretion samples were collected and calcium and total phosphorus concentrations were evaluated. At the same time, blood calcium, total phosphorus, sodium, potassium, chloride, magnesium concentrations and vitamin D were sampled. After intake of cola (1 L) over 180 min, gastric and duodenal secretion and blood were collected and characterized in order to analyse the amount of calcium and total phosphorus or sodium, potassium, magnesium and chloride ions, respectively. A strong pH decrease was observed after cola intake with an increase in phosphorus concentration. Consequently, a decrease in calcium concentration in gastric and duodenal secretions was observed. A decrease in calcium concentration was also observed in blood. In conclusion, we confirm that in patients with post-surgical hypoparathyroidism, the intake of large amounts of cola containing high amounts of phosphoric acid reduces calcium absorption efficiency despite the high doses of calcium therapy.